Analysis of the political system flow model in the ratification process of Net Zero Emissions (NZE) in Indonesia: Analisis model arus sistem politik dalam proses ratifikasi Net Zero Emissions (NZE) di Indonesia - Syuryansyah; Amalia, Ridha (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2025)
This article uses the Easton theory approach to analyse the political system flow model in Indonesia's Net Zero Emissions (NZE) Policy. The primary focus of this study is on the input, output, and feedback sections in the political system that support the NZE policy. The method used is qualitative with descriptive analysis to explain each section of the political system flow model. Data collection techniques are done through literature reviews, relevant articles, and news on handling climate change in Indonesia. Based on the results of the study, in the input section, there is significant support and demand from various parties, including the community, global social movements, the private sector, and international organisations such as the United Nations Framework Convention on Climate Change (UNFCCC). These diverse stakeholders play a crucial role in shaping and supporting the NZE policy. In the output section, various regulations and policies that have been ratified have been produced, such as the ratification of the 2016 Paris Agreement, the National Action Plan for Reducing Greenhouse Gas Emissions (RAN GRK), the National Energy General Plan (RUEN), and the REDD+ Initiative. In the feedback section, the output produced shows positive feedback from both the international and domestic communities, reflecting the effectiveness and acceptance of the NZE policy in Indonesia.